A Comparison of Random and Sinusoidal Vibration Effect on Human Alertness Level - Amzar Azizan, Mohd; bt Padil, Husna (International Journal of Engineering and Technology, 2018)
It is difficult to identify the means or models developed specifically to enlighten the society on what vibration can do to a normal human body â€“ one of the more popular vibrationsâ€™ effects is fatigue. As a form of impairment towards completing physical tasks, effects of fatigue have been studied extensively in various research settings and perspectives; especially concerning vehicle drivers. However, the distinct lack of prior studies on vibrationsâ€™ effects on seated driversâ€™ mental alertness has initiated our team to study further; having many confounding factors does make it complicated. Consequently, we began by ensuring the actual link between while-body vibration (WBV) and human drowsiness. For that, a custom-made setup was constructed specifically for testing human vibration. Low-frequency sweep sinusoidal and random whole-body radiation were used methodically on 10 volunteers. We set 0.3 ms-2 r.m.s. for 20 minutes because the values reflect perceived vibration which were experienced by the drivers. Electroencephalographic (EEG) signals would indicate if there is any kind of changes in drowsiness levels whereas the analysis was completed with two brainwave spectrums (theta waves and beta waves. The results proved that there is a link between WBV and drowsiness.Â Â